FAKTOR PENENTU PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Khoirun Nisak; Jaeni Jaeni (Faculty of Economic and Business Universitas STIKUBANK, 2019)
The purpose of this study is to examine the Determinants to Corporate Social Resposibility Disclosure in Manufacturing Companies listed on the Indonesia Stock Exchange. The dependent variable is Corporate Social Resposibility Disclosure. Independent variable are Firm Size, Liquidity, Profitability, Industrial Type, Managerial Ownership, and Size of Board of Commissioner. The population in this study was all Manufacturing Company listed on the Indonesia Stock Exchange in 2015-2017. Samples were 247 manufacturing companies. This study used purposive sampling method.The analysis used in this reseacrh are multiple linear regression analysis. The results of the testing of hypotheses partial evaluation shows that there are significant influence on Firm Size, Liquidity,Profitability, and Size of Board of Commisioner while for Industrial Type and Managerial Ownership not have significant influence to the Corporate Social Responsibility Disclosure. Keywords: firm size, liquidity, proftitability, industrial type, managerial ownership, size of board of commissioner, corporate social resposibility disclosure